2018
DOI: 10.1194/jlr.m085456
|View full text |Cite
|
Sign up to set email alerts
|

Circulating HDL levels control hypothalamic astrogliosis via apoA-I

Abstract: Meta-inflammation of hypothalamic areas governing energy homeostasis has recently emerged as a process of potential pathophysiological relevance for the development of obesity and its metabolic sequelae. The current model suggests that diet-induced neuronal injury triggers microgliosis and astrocytosis, conditions which ultimately may induce functional impairment of hypothalamic circuits governing feeding behavior, systemic metabolism, and body weight. Epidemiological data indicate that low circulating HDL lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 42 publications
1
6
1
Order By: Relevance
“…The association of vascular-specific GFAP (GFAP co-localized with CD31) with CAA was visualized using immunofluorescence and normalized to total cortical CAA area (e, g) and total vascular GFAP area (f, g) in the cortex. hypothalamic astrogliosis [60]; however, we did not observe any significant genotype effects on GFAP expression in the hypothalamus in the current study (Additional file 1: Figure S6a and b).…”
Section: Discussioncontrasting
confidence: 73%
“…The association of vascular-specific GFAP (GFAP co-localized with CD31) with CAA was visualized using immunofluorescence and normalized to total cortical CAA area (e, g) and total vascular GFAP area (f, g) in the cortex. hypothalamic astrogliosis [60]; however, we did not observe any significant genotype effects on GFAP expression in the hypothalamus in the current study (Additional file 1: Figure S6a and b).…”
Section: Discussioncontrasting
confidence: 73%
“…5). The increased concentration of cAMP induced by MC4R is thought to activate exchange protein directly activated by cAMP (EPAC), leading to ERK1/2-dependent phosphorylation of the transcription factor cAMP response element (CRE) binding protein (CREB), increased transcription of cFos and reduced phosphorylation and activity of AMPK (Glas et al 2016, Yang & Tao 2016. In this respect, intracerebroventricular delivery of the MC3R/MC4R synthetic agonists induces anorexia as well as activation of transcription by CREB and expression of cFos in the PVN (Thiele et al 1998, Benoit et al 2000, Harris et al 2001, Lee et al 2001, Sarkar et al 2002, Lu et al 2003, Rowland et al 2010.…”
Section: Mc4r and Mc3r Signalingmentioning
confidence: 99%
“…With this respect, decreased circulating high-density lipoprotein (HDL), a risk factor for cardiovascular disease, correlates with obesity (Woudberg et al 2016). When loss of HDL is simulated in mice by knockout of Apolipoprotein A1 (apoA-I), there is hypothalamic astrogliosis paralleled by disrupted hypothalamic mitochondrial function as well as by increased hepatic triglyceride content and glucose output (Gotz et al 2018). These data indicate that, in obesity, dyslipidemia with increased circulating saturated fatty acids and loss of HDL promotes hypothalamic inflammation and altered mitochondrial function in the hypothalamus.…”
Section: Role Of Increased Saturated Fatty Acids and Lipoproteins To mentioning
confidence: 99%
“…Indeed, astrocytes contain various immune pathways and can induce proinflammatory signaling and cytokine production via activation of glycoprotein 130, NF-kB, MAPK, and Jak/Stat1 pathways (Gorina et al, 2011;Haroon et al, 2011). Recently, it was recognized that obesity and related metabolic disorders are associated with astrogliosis, which might affect astrocytic functions (Buckman et al, 2013;Gö tz et al, 2018;Horvath et al, 2010;Kwon et al, 2017;Thaler et al, 2012). Research also showed that hypothalamic astrocytes from aged animals were more inflammatory Dalvi et al, 2017;Tsaousidou et al, 2014;Zhang et al, 2008 Inflammation affects regulatory signaling of AgRP neurons, leading to changes in energy and glucose disorders.…”
Section: Cellular Impacts Of Hypothalamic Microinflammationmentioning
confidence: 99%